2021
DOI: 10.4102/ac.v21i1.965
|View full text |Cite
|
Sign up to set email alerts
|

The association between ownership concentration and payout behaviour: Evidence from South Africa

Abstract: Orientation: The study investigated the association between ownership concentration and different payout methods of selected companies listed on the Johannesburg Stock Exchange (JSE) in South Africa for the financial reporting periods 2012 to 2019.Research purpose: The research objective was to investigate whether payout behaviour differed when low and high ownership concentration was compared.Motivation for the study: An understanding of the association between ownership concentration and payout policies is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…These findings confirm previous research showing that dividends are often omitted or reduced during economic or financial crises (Bozos et al, 2011;Forti & Schiozer, 2015). As mentioned earlier, the STC tax regime in South Africa changed to a dividend withholding tax (DWT) regime on 01 April 2012 (Nel et al, 2021). No statistically significant changes, however, occurred from 2011 to 2012 or from 2012 to 2013 in either the percentage of dividend payers or the average DPRs.…”
Section: The Trends In the Dividend Distributions And The Percentage ...supporting
confidence: 88%
See 2 more Smart Citations
“…These findings confirm previous research showing that dividends are often omitted or reduced during economic or financial crises (Bozos et al, 2011;Forti & Schiozer, 2015). As mentioned earlier, the STC tax regime in South Africa changed to a dividend withholding tax (DWT) regime on 01 April 2012 (Nel et al, 2021). No statistically significant changes, however, occurred from 2011 to 2012 or from 2012 to 2013 in either the percentage of dividend payers or the average DPRs.…”
Section: The Trends In the Dividend Distributions And The Percentage ...supporting
confidence: 88%
“…Company size and profitability were positively associated with the sampled companies' DPRs, whereas negative relationships were reported with sales growth and free cash flow (FCF). Furthermore, Nel et al (2021) observed that high ownership concentration was significantly related to lower ordinary dividends and capital distributions. Their sample included companies across three main industries, namely basic materials, industrials and financials.…”
Section: Earning Distributions In South Africamentioning
confidence: 99%
See 1 more Smart Citation